Implementation of Learning Activities Using Recycled Materials in Kindergarten - Apriliana, Nur Indah; Nofiandri Eko Sucipto Dwijo, Al-Qudus; Mukhoyaroh, Mukhoyaroh; Abdelkhalek, Shafa (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
Learning based on used materials for early childhood in an innovative approach that integrates environmental sustainability values with the development of creativity and fine motor skills. This study aims to describe the implementation of learning methods based on used materials in TK Muslimat NU Bunga Harapan, focusing on the benefits, challenges, and indicators of success. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the use of used materials, such as plastic, and kitchen waste, can support children's holistic development, skills, and recycling creativity. The obstacles faced include the limitations of certain used materials and children's negative perceptions of used materials as